PIGEONS' DELAY DISCOUNTING FUNCTIONS ESTABLISHED USING A CONCURRENT-CHAINS PROCEDURE - Oliveira, Luís (2014)
Several studies have examined discounting by pigeons and rats using concurrent-chains procedures, but the results have been inconsistent. None of these studies, however, has established that discounting functions derived from estimates of indifference points can be obtained with a concurrent-chains procedure, so their validity remains in doubt. The present study used a concurrent-chains procedure within sessions combined with an adjusting-amount procedure across sessions to determine the present, subjective values of food reinforcers to be obtained after a delay. Discounting was well described by the hyperbolic discounting function, suggesting that the concurrent-chains procedure and the more typical adjusting-amount procedure are measuring the same process. Consistent with previous studies with rats and pigeons using adjusting-amount procedures, no significant effect of the amount of the delayed reinforcer on the degree of discounting was observed, suggesting that the amount effect may be unique to humans although consistent with the view that animals' choices are controlled by the relative, rather than the absolute, value of reinforcers.